Предмет: Математика,
автор: ketri2
(3 1/3 + 2,5) * (4,6-2 1/3)
Ответы
Автор ответа:
0
(3 1/3 + 2,5) * (4,6 - 2 1/3) = (3 1/3 +2 1/2) * (4 6/10 - 2 1/3) =
(3 2/6 + 2 3/6) * (4 18/30 - 2 10/30) = (5 5/6) * (2 8/30) = 35/6 * 68/30 = 119/9 = 13 2/9
(3 2/6 + 2 3/6) * (4 18/30 - 2 10/30) = (5 5/6) * (2 8/30) = 35/6 * 68/30 = 119/9 = 13 2/9
Похожие вопросы
Предмет: Литература,
автор: tayabalashova01
Предмет: Геометрия,
автор: razumovanasta95
Предмет: Музыка,
автор: Wryef
Предмет: Математика,
автор: bakievimil